Prediction of Annual Rural Unemployment Rate in West Bengal using Grey Model - Pavithra V.; Deb Sankar Gupta; Pradip Basak; Manoj Kanti Debnath; Gobinda Mula (Journal of the Indian Society of Agricultural Statistics, 2025)
The rural unemployment rate is a critical economic indicator used to assess strength of rural economy in India. Annual estimates of rural UR are released in both usual status (ps+ss) as well as current weekly status (CWS) at the state and national level in India by National Statistics Office (NSO) through Periodic Labour Force Survey (PLFS). At present, the annual rural UR estimates are available for the state of West Bengal from the year 2017-18 to 2021-22. However, there is a notable delay in the publication of UR estimates as compared to the reference period. Therefore, accurate forecasting of the UR is crucial for timely and targeted interventions, and effective policy planning. Conventional forecasting models fail to provide accurate predictions of UR in these type of small time series due to the violation of requirement of number of data points. In contrast, the Grey model requires limited data to establish a differential forecasting model. In this study, application of grey model has been considered to forecast annual rural UR in West Bengal for different age groups as well as gender, and it was found that grey model provides satisfactory forecast.